Investigation of the disposal of dead pigs by pig farmers in mainland China by simulation experiment - Wu, Linhai; Xu, Guoyan; Li, Qingguang; Hou, Bo; Hu, Wuyang; Wang, Jianhua (Environmental science and pollution research international, 2017)
Dead pigs are a major waste by-product of pig farming. Thus, safe disposal of dead pigs is important to the protection of consumer health and the ecological environment by preventing marketing of slaughtered and processed dead pigs and improper dumping of dead pigs. In this study, a probability model was constructed for the disposal of dead pigs by pig farmers by selecting factors affecting disposal. To that end, we drew on the definition and meaning of behavior probability based on survey data collected from 654 pig farmers in Funing County, Jiangsu Province, China. Moreover, the role of influencing factors in pig farmers’ behavioral choices regarding the disposal of dead pigs was simulated by simulation experiment. The results indicated that years of farming had a positive impact on pig farmers’ choice of negative disposal of dead pigs. Moreover, there was not a simple linear relationship between scale of farming and pig farmers’ behavioral choices related to the disposal of dead pigs. The probability for farmers to choose the safe disposal of dead pigs increased with the improvement of their knowledge of government policies and relevant laws and regulations. Pig farmers’ behavioral choice about the disposal of dead pigs was also affected by government subsidy policies, regulation, and punishment. Government regulation and punishment were more effective than subsidy. The findings of our simulation experiment provide important decision-making support for the governance in preventing the marketing of dead pigs at the source.